Fabrication of Surface Layer Enriched with Zinc on AlSi17 Aluminium Cast Alloy by Hot-Dip Galvanizing - Bucki, Tomasz; Bolibruchová, Dana (Journal of Casting & Materials Engineering, 2020)
The paper deals with the fabrication of the surface layer enriched with Zn on AlSi17 aluminium alloy to modify the microstructure and surface properties of the alloy. The continuous surface layer was fabricated on the AlSi17 substrate by the hot-dip galvanizing of AlSi17 for 15min in a Zn bath heated to 450°C. The thickness of the layer was about 100 μm. The layer was characterised by a multi-component microstructure containing the regions of a solid solution of Al in Zn and dendrites of a eutectoid composed of a solid solution of Al in Zn and a solid solution of Zn in Al. In the layer, fine particles of Si with a regular shape were distributed. The results indicated that these Si particles formed by the action of Zn on the eutectic Si precipitations in the AlSi17 substrate. In the microstructure, large primary Si crystals and multi-phase precipitations, originating from the substrate, were also observed. The surface layer had much higher microhardness than the AlSi17 substrate. The results showed that hot-dip galvanizing can be used to modify the microstructure and properties of the surface layer of AlSi17. The study indicates the possibility of conducting further research on the fabrication of joints between AlSi17 and other metallic materials using a Zn interlayer fabricated by hot-dip galvanizing.